Pheophytin analogues from the medicinal lichen Usnea diffracta. Issue 9 (3rd May 2018) - Xu, Hong-Bo; Yang, Tong-Hua; Xie, Pei; Liu, Shi-Jun; Liang, Yan-Ni; Zhang, Yu; Song, Zhong-Xing; Tang, Zhi-Shu
Abstract: A new pheophytin, (13 2 S, 17 S, 18 S )-13 2 -hydroxy-20-chloro-ethylpheophorbide a (3 ), along with two known analogues (1 –2 ) were isolated from the lichen Usnea diffracta Vainio (Parmeliaceae). Among them, compound3 was a rare C-20-chloro type pheophytin obtained from lichens. Their structures were elucidated by extensive spectroscopic analysis, and all the compounds were obtained for the first time from U. diffracta . Compounds (1 –3 ) were evaluated for their xanthine oxidase (XO) inhibitory activities in vitro, and the results showed that1–3 possessed significant enzyme inhibitory actions with IC50 values of 46.9 ± 3.8, 75.9 ± 7.4 and 42.1 ± 1.7 μg/mL, respectively. Abstract :